Follow-up Evaluation of Air Force Blood Donors Screening Positive for Chagas Disease. (4th October 2017) - Marcus, Joseph; Cropper, Thomas; Webber, Bryant; Wilson, Matthew; Yun, Heather
Abstract: Background: Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, is endemic to Texas and has significant morbidity associated with its cardiac pathology. The Joint Base San Antonio-Lackland (JBSA) represents a healthcare system with universal coverage to its beneficiaries and its blood bank screens all first-time blood donors for T. cruzi infection. Although there is a published, standardized approach for diagnosis and evaluation of Chagas disease in the United States, adherence to this approach has not been studied. Methods: A retrospective chart review was performed on all persons who screened positive for T. cruzi on blood donation at JBSA from 2014 to 2016. Charts were reviewed to determine frequency and results of confirmatory testing, history and physical, EKG, and 30 second rhythm strip; outcomes of these evaluations were ascertained. Chagas disease was considered confirmed on the basis of positive EIA and TESA testing from the CDC and/or two different positive serologic tests. Results: Of the 43, 402 blood donors at JBSA, 23 screened positive for Chagas disease. Follow-up information was available on 22 (95.7%). Seventeen (77%) were military trainees and 18 (82%) were male. Patients had a mean of 2.5 (range 1–5) additional serologic tests, with 13 different combinations of confirmatory tests ordered, including 17 (77%) who had the initial screening test repeated. Two patients (9%), both from Texas, met criteria for Chagas disease. One of these was diagnosed with cardiomyopathy and underwent administrative separation from the Air Force. Eleven (50%) had Chagas disease excluded on the basis of two negative follow-up tests, and 9 (41%) had one negative follow-up test. All underwent history and physical, 15 (68%) had an EKG, and 5 (22%) had a 30 second rhythm strip. Fourteen (64%) were referred to infectious diseases. Conclusion: Among a small cohort of active duty service members who screened positive for T. cruzi infection on blood donation, diagnostic workup, and evaluation varied considerably, despite universal access to no-cost medical care within a single system. Opportunities exist within the military health system to decrease heterogeneity and to improve evaluation of persons who screen positive in the future. Disclosures: H. Yun, American Board of Internal Medicine, Infectious Disease Board: Board Member, travel reimbursement, honorarium